UPAYA MENINGKATKAN KETERAMPILAN MEMUKUL BOLA KASTI MELALUI METODE PEMBELAJARAN MODIFIKASI PADA SISWA KELAS IV SDN RUNGKUT MENANGGAL II/583 SURABAYA - KETUT ARDANA, GUSTI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Baseball is a game of small ball because it uses small balls the size of tennis balls.  The game is held in the open field. In children of primary school age, the game can  t rain the self-discipline and foster a sense of togetherness and solidarity among friends. To be able to play baseball well we are required to have some skill that is hitting,throwing, and catching the ball and the ability to run. In SDN Rungkut Menanggal   II/583 Surabaya  baseball game can not be understood by the students, so that the necessary learning model that uses a modification of the ball, so students can practice well, because the modified ball is lighter than the actual baseball. For that researchers will develop a learning tool in the modification of a baseball game which will be used  as a reference by the teacher in providing learning materials penjas rounders.            Keywords: application of modified, baseball